Wide range modulation indexes featuring carrier-based PWM stepped waveform for half-bridge modular multilevel converters - Tohtayong, Majdee; Khan, Sheroz; Yaacob, Mashkuri; Yusoff, Siti Hajar; Midi, Nur Shahida; Ahmed, Musse Mohamud (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
This paper presents simulation results of the influence of wide range modulation index values ( a m ) in carrier-based PWM strategy for application in generating the stepped waveform. The waveform is tested for application in single-phase half-bridge modular multilevel converters (MMCs) topology. The results presented in this paper include a variation of the fundamental component (50 Hz) in the voltage output. It also studies total harmonic distortion of the output voltage (THDv) and the output current (THDi) when the modulation index is changed over the linear-modulation region, 0 < a m < 1. It also explores the effect of a modulation index greater than 1. Moreover, different output voltage shapes, as a consequence of varied a m on MMCs, are also illustrated for showing the effect of varying the value of a m on sub-module of MMC's. *********************************************************** Kajian ini berkenaan tentang pengaruh simulasi terhadap pelbagai nilai indeks ( ) berasaskan strategi PWM bagi menghasilkan bentuk gelombang bertingkat. Bentuk gelombang ini diuji untuk aplikasi topologi MMCs. Keputusan menunjukkan variasi pada komponen asas (50Hz) pada voltan akhir. Keputusan menunjukkan jumlah penyelarasan harmonik voltan akhir (THDv) dan arus (THDv) apabila indeks modulasi telah ditukar pada had modulasi linear, 0 < < 1. Ia juga membincangkan tentang kesan indeks modulasi lebih daripada 1. Selain itu, bentuk voltan akhir yang berbeza mengikut perubahan nilai pada MMCs juga dilampirkan bagi menunjukkan kesan perbezaan nilai pada sub-modul MMCs.